Using textual and structural context for searching Multimedia Elements. (25th October 2010) - Torjmen, Mouna; Pinel-Sauvagnat, Karen; Boughanem, Mohand
We investigate in this paper the use of XML structure in multimedia retrieval, particularly in context-based image retrieval. We propose two methods to represent multimedia objects: the first one is based on an implicit use of textual and structural context of multimedia objects, whereas the second one is based on an explicit use of both sources. Experimental evaluation is carried out using the INEX MultimediaFragments Task 2006 and 2007. We show that there is a strong vocabulary relation between the query and the multimedia object representation, and that using XML structure improves significantly the effectiveness of multimedia retrieval.